Two new species of Stigmaeidae (Acari: Trombidiformes: Rhaphignathoidea) from Brazil - Paktinat-Saeij, Saeid; Barroso, Geovanny; Cruz, Wilton Pires da [UNESP] (Magnolia Press, 2017)
Two new species of Stigmaeidae, Agistemus rodriguezi Paktinat-Saeij & Cruz sp. nov. and Eryngiopus moraesi PaktinatSaeij & Barroso sp. nov. are described and illustrated on the basis of adult specimens from northern Brazil.
Keywords: Prostigmata; Agistemus; Eryngiopus; predatory mites; systematics; Amazonas State; Alagoas State